SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/133033-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nano-emulsions as Cement Spacer Improve the Cleaning of Casing Bore During Cementing Operations

Abstract: Nano-emulsions are emulsions where the droplet size of internal phase is less than 500 nm. Due to their small dimensions they have a high surface area and show very peculiar properties. Solvent in water nano-emulsions combine the high efficiency of the small dimensions of solvent to a low interfacial tension, due to the presence of the surfactant mixture used to prepare nanoemulsions. Solvent in water nano-emulsions used as cement spacer formulation could allow optimizing the cleaning of the casing during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…As the engineered nanostructures have high mechanical strength, these structures can be used in making of down hole tools so that the tools can be run in hostile environments. Spacers with nano emulsions in cementing operations can also be optimized by using nanoparticles so that hole cleaning can be carried out effectively during cementing [18]. Several nanoparticles such as nanosilica, nanoalumina and carbon nanotube (CNT) have been studied to improve the performance of cement with respect to its hydration process, fluid loss, gas migration and compressive strength [19].…”
Section: Drilling and Completionmentioning
confidence: 99%
“…As the engineered nanostructures have high mechanical strength, these structures can be used in making of down hole tools so that the tools can be run in hostile environments. Spacers with nano emulsions in cementing operations can also be optimized by using nanoparticles so that hole cleaning can be carried out effectively during cementing [18]. Several nanoparticles such as nanosilica, nanoalumina and carbon nanotube (CNT) have been studied to improve the performance of cement with respect to its hydration process, fluid loss, gas migration and compressive strength [19].…”
Section: Drilling and Completionmentioning
confidence: 99%
“…Nano-emulsions, the droplet size of which was between 20 and 500 nm, were obtained by a low energy cost method, so they could be prepared readily in great amounts (Maserati et al, 2010). In addition, the nano-emulsions could be directly obtained in the field or transported on site.…”
Section: New Nano-spacer Fluidsmentioning
confidence: 99%
“…These systems are considered thermodynamically stable, transparent, or translucent, with low interfacial tension, due to the presence of surfactant compounds at the oil/water interface [15,16]. Previous research has shown the application of microemulsions can be used as cleanup fluids: to solubilize the oil present in the drilling mud [17]; in the filter cake removal and wettability inversion [9][10][11][12][18][19][20].…”
Section: Introductionmentioning
confidence: 99%